Syphilis Infection Differentially Regulates the Phenotype and Function of γδ T Cells in HIV-1-Infected Patients Depends on the HIV-1 Disease Stage - Li, Zhen; Lu, Xiaofan; Hu, Zhiliang; Luo, Zhenwu; Jiang, Wei; Wu, Hao; Gao, Yanqing; Yan, Junling; Zhang, Qiuyue; Song, Aixin; Huang, Xiaojie; Mou, Danlei; et al. (Frontiers in Immunology, 2017)
A rapidly escalating outbreak of syphilis infection has been affected men who have sex with men, particularly those with HIV-1 infection. γδ T cells are unconventional immune cells with two main subsets, Vδ1 T cells and Vδ2 T cells, which possess a combination of innate and adaptive immune features allowing them to against HIV. However, whether syphilis infection affects the phenotype and function of γδ T cells in HIV-1-infected patients remains unclear, especially in acute HIV-1 infection (AHI). In this study, we enrolled 57 HIV-1-infected patients (24 with HIV-1 infection only and 33 co-infected with syphilis) from an acute HIV-1-infected cohort in Beijing (PRIMO). A comprehensive analysis of γδ T-cell phenotype and function was performed by flow cytometry. We found syphilis co-infection could reverse the imbalance of Vδ1/Vδ2 ratio in AHI. Syphilis infection results in decreased γδ T-cell activation in AHI, but increased γδ T-cell activation in chronic HIV-1 infection (CHI). Moreover, patients with CHI had larger numbers of IL-17-producing γδ T cells than those with AHI, regardless of syphilis status. Thus, syphilis affected the γδ T-cell immune response differently in patients depending on the stages of HIV-1 disease. In addition, the percentage of IL-17-producing γδ T cells was positively correlated with the percentage of neutrophils. These results suggest that the γδ T-cell/IL-17/neutrophil axis is involved in HIV-1 pathogenesis and disease progression. Taken together, our observations provide new insight into the roles of γδ T cells in immunopathogenesis of syphilis and HIV co-infection, particularly during AHI, and our findings may be helpful for the prevention of syphilis and other sexually transmitted infections and highlight the great significance on the remedy of patients co-infected with HIV.